Effect of a mobile application-based whole-course nutrition management intervention in patients with age-related macular degeneration: a randomized controlled trial - Wenmei Guo; Junli Wan; Feng Zhang; Xuemei Wu; Yan Hong; Zonghua Wang; Wei Bian (Frontiers in Public Health, 2026)
Aims and objectives Evaluate the effect of the application (APP)-based AIM-AMD (Assessment, Introduction, Management, and App-based Maintenance Dynamically) nutrition management model in patients with age-related macular degeneration (AMD). Background Nutritional intervention are one of the only ways to prevent the development of AMD and slow its progression. However, poor compliance with patient nutritional management leads to ineffective nutritional supplementation outcomes. Design A randomised controlled trial was conducted from October 2023–January 2024 and performed according to the CONSORT guidelines. Methods A total of 140 participants were randomly assigned to the intervention or control group. The intervention was administered three times per week for a period of 3 months. The intervention group was adopted with APP-based AIM-AMD nutrition management + routine nursing, while the control group was adopted with routine nursing. Comparison was conducted on the effects of different programs on AMD patient nutrient intake, nutrition knowledge, vision-related quality of life, self-efficacy and best-corrected visual acuity (BCVA) at the beginning and at the end of the intervention (Clinical Trials.gov: ChiCTR2200063978). Results The results indicated that the intake of energy, zinc, copper, calcium, vitamin C, vitamin E and lutein was significantly higher in the intervention group than in the control group ( p < 0.001). The intake of protein was significantly higher in the intervention group than in the control group ( p < 0.01), whereas the intake of fat was significantly lower in the intervention group ( p < 0.001). However, there were no significant differences in the intakes of iron, vitamin A, vitamin D, or folic acid between the intervention and control group. Vision-related quality of life, nutritional knowledge and self-efficacy scores of intervention group were higher than that of control group ( p < 0.001). The BCVA of the intervention group did not differ significantly from that of the control group ( p > 0.05). Conclusion Our research demonstrates that the APP-based AIM-AMD nutrition management model offers patients comprehensive, accurate, and personalized guidance on dietary management. Relevance to clinical practice The results of this study demonstrate that the AIM-AMD nutritional management model holds demonstrable clinical value in the nutritional management process of patients with AMD. Clinical trial registration https://www.chictr.org.cn/showproj.html?proj=175931 , Identifier ChiCTR2200063978.